The potential effect of HBV vaccination on off-treatment HBsAg reversion after interferon-induced HBsAg clearance. Issue 1 (31st December 2023) - Jiang, Shaowen; Cai, Minghao; Zhang, Zhenglan; Qian, Cong; Wang, Jiexiao; Li, Ziqiang; Guo, Qing; Zhou, Huijuan; Xin, Haiguang; Cai, Wei; Wang, Hui; Guo, Simin; et al.
ABSTRACT: Off-treatment HBsAg reversion occurs in a considerable number of chronic hepatitis B(CHB) patients after IFN(interferon)-induced HBsAg clearance. HBV vaccination protects the general population against HBV infection. However, it remains unclear whether HBV vaccination could prevent off-treatment HBsAg reversion in CHB patients with HBsAg clearance. CHB patients (n = 199) with HBsAg clearance were included in the current study, comprising spontaneous HBsAg clearance group (n = 51), NA (nucleoside/nucleotide analogues)-induced group (n = 36) and IFN-induced group (n = 112). Log-rank test was performed to compare the cumulative incidences of HBsAg reversion between groups. Cox regression model was used to identify the factors associated with off-treatment HBsAg reversion. The 5-year cumulative incidence of HBsAg reversion in IFN-induced group was significantly higher than that in NA-induced group or spontaneous group (27.6% vs . 3.3% vs . 8.1%, both p  < .05). In IFN-induced group, 66.7% of CHB patients received HBV vaccination. The cumulative incidence of HBsAg reversion in individuals with strong responses to HBV vaccination (HBsAb level >100mIU/ml) was significantly lower than that in those with weak responses to HBV vaccination (HBsAb level ≤100mIU/ml) or without HBV vaccination in IFN-induced group (7.7% vs . 58.5% vs . 31.9%, both p  < .05). Multivariate Cox regression analysis confirmed strong responses to HBV vaccination were independently associated with a lower cumulative incidence of HBsAg reversion after IFN-induced HBsAg clearance (HR = 0.246, 95%CI: 0.066–0.907, p  = .035). HBV vaccination has potential to prevent off-treatment HBsAg reversion in CHB patients after IFN-induced HBsAg clearance via a sufficiently high level of HBsAb, helping clinicians optimize the clinical management of such patients.